SUSTAINABILITY PERFORMANCE, GREEN INNOVATION AND ECO-EFFICIENCY ON COMPANY VALUE WITH COMPREHENSIVE PROFITABILITY AS MODERATION - Mujati Suaidah, Yuniep; Kusuma, Marhaendra (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2026)
Research so far has still provided inconsistent results on the role of profitability moderation in the influence of sustainability performance, green innovation and eco-efficiency on firm value, and does not involve comprehensive profit and attributable profit in the profitability formulation, even though the meaning of profit has shifted since the implementation of fair value accounting and entity theory in financial reporting. The purpose of this study is to test the role of profitability moderation, which is formulated with comprehensive profit and attributable profit, in the influence of sustainability performance, green innovation and eco-efficiency on firm value. The research sample was 141 companies listed on the Indonesia Stock Exchange 2019 - 2023 with 553 observation data. Hypothesis testing with Moderation Regression Analysis. The results of the study indicate that profitability based on comprehensive profit and attributable profit strengthens the influence of sustainability performance, green innovation, and eco-efficiency on firm value. The originality of this study is testing the role of profitability moderation based on comprehensive profit and attributable profit in the influence of sustainability performance, green innovation and eco-efficiency on firm value